AKIBAT HUKUM TERHADAP PENYALAHGUNAAN VISA MASUK BAGI ORANG ASING DI KANTOR IMIGRASI DENPASAR - Oka Bayu Aditya Kuntala, Putu; Artha, I Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013, 2013)
Legal consequences of the misuse of entry visas to foreigners at Immigrationoffice Denpasar regulated in Act No. 6 of 2011. This paper aims to The use ofsurveillance and Visa Entry Permit for Foreigners the method used is emperis isdoing field research by interviewing the relevant parties. The use of surveillance andVisa Entry Permit for Foreigners include: Entry and exit of foreigners to and fromthe territory of Indonesia; existence and activities of foreigners in the territory ofIndonesia. Legal consequences arising against the misuse of visas and entry permitsBy Foreign Nationals in the Immigration Office can be given administrativesanctions and criminal sanctions.
Keywords: entry visa, stranger, sanctions law